2017
DOI: 10.1371/journal.pntd.0005501
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests duo as alternative to conventional serological assays for conclusive Chagas disease diagnosis

Abstract: Chagas disease is caused by the parasite Trypanosoma cruzi. It affects several million people, mainly in Latin America, and severe cardiac and/or digestive complications occur in ~30% of the chronically infected patients. Disease acute stage is mostly asymptomatic and infection goes undiagnosed. In the chronic phase direct parasite detection is hampered due to its concealed presence and diagnosis is achieved by serological methods, like ELISA or indirect hemagglutination assays. Agreement in at least two tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 17 publications
11
97
1
3
Order By: Relevance
“…This, coupled with the high FOI estimate, demonstrates significant recent vector transmission. Although the specificity of the CDP (91.9%) in this study was lower than that reported in previous analyses, screening in this rural village was greatly facilitated by the use of this rapid test (Eguez et al, 2017;Shah et al, 2014). Pairing a highly sensitive rapid test with a more specific confirmatory test allows efficient screening, even in a challenging community setting.…”
Section: Discussioncontrasting
confidence: 62%
“…This, coupled with the high FOI estimate, demonstrates significant recent vector transmission. Although the specificity of the CDP (91.9%) in this study was lower than that reported in previous analyses, screening in this rural village was greatly facilitated by the use of this rapid test (Eguez et al, 2017;Shah et al, 2014). Pairing a highly sensitive rapid test with a more specific confirmatory test allows efficient screening, even in a challenging community setting.…”
Section: Discussioncontrasting
confidence: 62%
“…Promising progress toward the development of better diagnostics has been reported in recent years, with validation of rapid diagnostic tests (RDTs) showing similar performance to classical serological tests. RDTs have the additional benefit of requiring less trained personnel and laboratory infrastructure [ 23 ]. Table 1 summarizes potential strategies for improving the PPC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first, we deeply agree with the concerns of the letter authors on the reduced access to Polymerase Chain Reaction (PCR) and conventional serology (ELISA) tests for the diagnosis of Chagas disease in many areas where the disease is highly endemic and only poorly equipped laboratories are available. In fact, our team at ISGlobal is working at present in a research line which aims to show that the use of alternative diagnostic methodologies, easier to use in those regions, can indeed substitute conventional diagnostics [4,5]. This is, in our opinion, the most urgent necessity in relation to Chagas disease diagnostics at the moment: validation and implementation of rapid diagnostic tests (RDTs) to diagnose chronic infections, and easy-to-use molecular tools such as loop mediated isothermal amplification (LAMP) to early detect congenital transmission events [6].…”
Section: Letter To the Editormentioning
confidence: 99%